History of meteorology in Bavaria 1400–1900. (10th January 2023) - Winkler, Peter
Abstract : In Bavaria, early weather observations date back to 1587, the reason for which was a series of very cool years. Contemporarily, witches were burned because they were thought to have influenced weather. After instruments became available, private observations started in 1718 and from 1781 to 1800 a network with 34 stations was set up by the Bavarian Academy of Sciences. Another network with 170 stations was run from 1842 to 1844. In 1878, a governmental netwo was installed fulfilling the scientific requirements.